Increased accuracy of single photon emission computed tomography (SPECT) myocardial perfusion scintigraphy using iterative reconstruction of images - Stević, Miloš Ljubomir; Vlajković, Marina (Vojnosanitetski pregled, 2017)
Background/Aim. Filtered back projection (FBP) is a common way of processing myocardial perfusion imaging (MPI) studies. There are artifacts in FBP which can cause false-positive results. Iterative reconstruction (IR) is developed to reduce false positive findings in MPI studies. The aim of this study was to evaluate the difference in the number of false positive findings in MPI studies, between FBP and IR processing. Methods. We examined 107 patients with angina pectoris with MPI and coronary angiography (CAG), 77 man and 30 woman, aged 32−82. MPI studies were processed with FBP and with IR. Positive finding at MPI was visualization of the perfusion defect. Positive finding at CAG was stenosis of coronary artery. Perfusion defect at MPI without coronary artery stenosis at CAG was considered like false positive. The results were statistically analyzed with bivariate correlation, and with one sample t-test. Results. There were 20.6% normal, and 79.4% pathologic findings at FBP, 30.8% normal and 69.2% pathologic with IR and 37.4% normal and 62.6% pathologic at CAG. FBP produced 19 false-positive findings, at IR 11 false positive findings. The correlation between FBP and CAG was 0.658 (p
Keywords: angina pectoris; diagnosis; scintigraphy; coronary angiography; technology; medical; methods